Ethnocentrism in Edward Zwick’s The Last Samurai Movie: Postcolonial Perspective - Ali - Mustofa (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2021)
This research focuses on ethnocentrism in Edward Zwick’s The Last Samurai. It is intended to identify how ethnocentrism is depicted and reflected in the life of samurai in the movie The Last Samurai. The ethnocentrism theory by William G. Sumner will be used to analyze the movie. The data were obtained by watching the film, reading the movie script and cinematographic elements, identifying data based on the topic of study, and categorizing the data with respect to the theoretical framework. Based on the analysis, the findings show that there are three aspects of ethnocentrism; first, loyal to in-group norms; second, express in-group pride; third, judge and underestimate the out-group. These three features of ethnocentrism create a deep perception in their dominant culture to others.